Historical changes in organic matter input to the muddy sediments along the Zhejiang-Fujian Coast, China over the past 160 years. (September 2017) - Chen, Lilei; Liu, Jian; Xing, Lei; Krauss, Ken W.; Wang, Jiasheng; Xu, Gang; Li, Li
Highlights: Two cores with good sedimentation rate records from coastal mud area were studied. Paleoenvironmental multiproxy indices were developed and applied. Anthropogenic activity markedly influenced terrestrial input proportion and marine productivity. Diagenesis affected quantitative calculation of relative contribution of various organic matter sources. Climate events had a good record in the core sediments. Abstract: The burial of sedimentary organic matter (SOM) in large river-influenced estuarine-coastal regions is affected by hydrodynamic sorting, diagenesis and human activities. Typically, the inner shelf region of the East China Sea is a major carbon sink for the Yangtze River-derived fine-grained sediments. Most of the previous work concentrated on studies of surface sediments or used a single-proxy in this region. In this study, two cores from the Zhejiang-Fujian Coast were analyzed using bulk (TOC, TN and δ 13 CTOC ) and molecular biomarker ( n -alkane, brassicasterol, dinosterol and glycerol dialkyl glycerol tetraether lipids) techniques to clarify the sources, spatiotemporal distribution and fate of SOM in the Yangtze River Estuary and adjacent shelf. Results indicated that the effects of diagenesis and diffusion on different sedimentary biomarkers resulted in overestimation of the relative contribution of terrestrial organic matter (%OMterr ), compared with those based on δ 13 CTOC . The amount of terrestrial plant organic matter (OMplant ) and %OMterr in sediments decreased offshore. In contrast, the amount of marine organic matter (OMmarine ) increased offshore, but closer to the Yangtze River mouth, the amount of soil organic matter (OMsoil ) increased. Moreover, the amounts of TOC, OMplant and OMmarine biomarkers increased, but OMsoil and %OMterr decreased over time in recent decades. Our study suggests that spatial OM distribution patterns in marine shelf sediments were controlled primarily by hydrodynamic sorting and nutrient concentration, and temporally diverse patterns were controlled predominantly by anthropogenic influence (e.g. dam construction and soil conservation, reclamation and agricultural plantations, anthropogenic nutrient input, dust storms, eutrophication, etc.) and climate events (e.g. interdecadal climatic jump and heavy rain events) in the geological period.